Economic Growth and Verdoorn's Law in the Spanish Regions, 1962-1991 - Miguel A. Leon-Ledesma (University of Kent, Department of Economics, 1998)
The aim of this paper is to test for the presence of dynamic increasing returns to scale in Spanish regional growth between 1962 and 1991. The theoretical framework within which this paper is based is the so-called Verdoorn's Law. Tests of the law are performed not only for the manufacturing sector but also for agriculture, construction, services and total value added. The results show substantial increasing returns for manufacturing for the services sector and for total value added. The static-dynamic paradox found by McCombie (1982) is also discussed and tested. We find no support for the hypothesis of a Cobb-Douglas as the underlying technical relationship of the law.
Keywords: O40; O47; R11; 330; Regional growth; Verdoorn's Law; Sectoral Disaggregation; Regionales Wachstum; Skalenertrag; Industrie; Schätzung; Theorie; Spanien